Rhodium-catalysed arylative cyclisations of malonate esters by 1,4-rhodium migration - O'Brien, Luke (2019)
Rhodium-catalysed intramolecular arylative cyclisations of malonate esters, generating highly functionalised bicycles has been described. The key step is a known alkenyl-to-aryl 1,4-rhodium migration. The reaction is considered to proceed through regioselective carbometallation of the tethered alkyne, followed by alkenyl-to-aryl 1,4-migration and subsequence intramolecular 1,2-addition to the ester moiety. Discovery and preliminary results were conducted by Dr. S. Karad. Through the use of a bisphosphine base ligand, good levels of enantiocontrol were achieved.